TRANSFORMATION OF ISLAMIC RELIGIOUS COUNSELORS' DA'WAH IN THE POLICIES OF THE MINISTRY OF RELIGIOUS AFFAIRS IN INDONESIA - Supriyadi, Dedi; Hamid, Abdul; Uyuni, Badrah; Farooq, Hafiz Shuaib (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The development of Islamic preaching continues to change. The transformation of Islamic preaching by Islamic religious instructors is an important part of the Ministry of Religious Affairs' response to the socio-religious dynamics in Indonesia. This transformation positions Islamic preachers as social facilitators and agents of change who not only convey religious teachings but also mediate conflicts, strengthen tolerance, and empower communities. The transformation of Islamic preaching by Islamic preachers is a strategic step in improving the quality of religious guidance amidst social changes in society. This study focuses on the implementation of the Ministry of Religious Affairs' extension policy in Pondok Melati District, Bekasi City, an area with growing religious dynamics and social diversity. The research method used is descriptive qualitative, with data collection techniques through field observations, interviews with functional and non-functional religious instructors, and a review of extension program documents at the Office of Religious Affairs (KUA). The results show that the transformation of Islamic preaching in Pondok Melati is characterized by a shift in approach from lecture-based preaching to a model of mentoring and community empowerment. Extension preaching functions as a bridge between state policy and the real needs of the people, thus strengthening the role of religion as a transformative force in socio-religious development in Indonesia.